Information processing and management of uncertainty in knowledge-based systems. 16th International Conference, IPMU 2016, Eindhoven, the Netherlands, June 20-24, 2016, Proceedings /: 16th International Conference, IPMU 2016, Eindhoven, the Netherlands, June 20-24, 2016, Proceedings. Part II : (2016) - Unknown
No abstract available